Prevalence of overweight and obesity in professional soldiers of the Czech Army over an 11-year period - Fajfrová, Jana; Pavlík, Vladimír; Psutka, Jan; Husárová, Michaela; Krutišová, Pavla; Fajfr, Miroslav (Vojnosanitetski pregled, 2017)
Background/Aim. Obesity is currently considered to be the most frequent metabolic disease worldwide, not only in developed but also in developing countries. The aim of this work was to describe the development of health status in soldiers of the Armed Forces of the Czech Republic (ACR) and to emphasize the markers of non-communicable diseases. Our study describes the anthropometric and biochemical parameters of a large group of Czech Army professional soldiers. Data were obtained over a period of 11 years. Methods. During the monitored period, from 1999 to 2009, military physicians carried out on the average 6,360 examinations on professional soldiers per year and monitored their health and nutritional status with the aim of preventing the risk factors of non-communicable diseases. These examinations are compulsory for all professional soldiers at the age of 25, 30, 33, and 36 years. From the age of 39, these examinations are carried out every year till the end of their career. Besides taking personal histories and carrying out standard physical examinations, blood was taken for biochemical examination. The following anthropometric parameters were monitored: body constitution using body mass index (BMI) and waist circumference. Our study describes only part of the data concerning anthropometric and biochemical parameters of professional soldiers which were obtained over a period of 11 years. Results. Average BMI values in men were in the overweight range (26.5–27 kg/m2). Average values of waist circumference, however, ranged from 91.9 cm to 93.4 cm. Between the first and the last year of monitoring a statistically significant decrease in these values ranging from 93.4 ± 9.8 cm to 92.7 ± 9.5 cm (p < 0.001) was observed. All monitored anthropometric parameters in female professional soldiers were within normal limits. During the monitored period the proportion of overweight men gradually increased from 52% to 57.1% (p < 0.001). There were no statistically significant changes in the prevalence of obesity in men (12–15%). Average glycaemia levels were within normal range in both men and women. A statistically significant decrease in these levels, however, was observed in men (from 5.1 ± 0.9 mmol/L to 4.8 ± 0.7 mmol/L (p < 0.001) and in women (from 4.9 ± 0.6 mmol/L to 4.6 ± 0.6 mmol/L (p < 0.001). Concerning the lipid profile in men, a significant decrease in average values of total cholesterol, triglycerides and LDL cholesterol was observed; from 5.5 ± 1.1 mmol/L to 5.1 ± 1.0 mmol/L (p < 0.001), from 2.0 ± 1.6 mmol/L to 1.6 ± 1.2 mmol/L (p < 0.001) and from 3.4 ± 1.1 mmol/L to 3.2 ± 0.9 mmol/L (p < 0.001), respectively. Conclusion. During the monitored period only one-third of military professionals had normal body weight. More favorable situation was in female professional soldiers, two-thirds of them had normal body weight during the monitored period. Additionally, the increase in the number of individuals with BMI values in the overweight range was observed. Although the number of overweight soldiers was overestimated as a result of the inclusion of individuals with increased body weight due to well-developed musculature, the number of overweight and obese soldiers is still high.